2022
DOI: 10.1177/20417314221105305
|View full text |Cite
|
Sign up to set email alerts
|

Liver scaffolds obtained by decellularization: A transplant perspective in liver bioengineering

Abstract: Liver transplantation is the only definitive treatment for many diseases that affect this organ, however, its quantity and viability are reduced. The study of liver scaffolds based on an extracellular matrix is a tissue bioengineering strategy with great application in regenerative medicine. Collectively, recent studies suggest that liver scaffold transplantation may assist in reestablishing hepatic function in preclinical diseased animals, which represents a great potential for application as a treatment for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 131 publications
1
9
0
Order By: Relevance
“…Both aged livers and low and high steatosis livers were successfully decellularized as all livers had less than 50 ng DNA per mg tissue, which is the standard to establish sufficient decellularization, [15] along with the absence of nuclear content in H&E staining. [16] Histological analysis of the livers showed, consistent with our earlier findings, that aged livers had a denser ECM structure and higher collagen content compared to young livers. We observed the opposite pattern with increasing steatosis levels.…”
Section: Discussionsupporting
confidence: 91%
“…Both aged livers and low and high steatosis livers were successfully decellularized as all livers had less than 50 ng DNA per mg tissue, which is the standard to establish sufficient decellularization, [15] along with the absence of nuclear content in H&E staining. [16] Histological analysis of the livers showed, consistent with our earlier findings, that aged livers had a denser ECM structure and higher collagen content compared to young livers. We observed the opposite pattern with increasing steatosis levels.…”
Section: Discussionsupporting
confidence: 91%
“…To resemble functional liver tissue, the transplanted ALS should undergo remodeling to ensure its tissue mechanical properties; therefore, the production of structural ECM proteins is crucial. The liver contains important ECM constituents, such as fibrillar collagens (types I and III) [ 6 , 14 ]. In this study, we observed that cells in the graft produced neo-ECMs (collagen I and reticular fibers) after ALS transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have focused on the recellularization steps before transplantation, ALS transplantation itself has only been partially explored. Although total orthotopic transplantation of ALS would not support the metabolic demands of patients after transplantation, other alternatives can be explored to find new therapeutic tools in the fields of hepatology and regenerative medicine [ 6 ]. For example, ALS could be applied after partial hepatectomy to increase the limit of liver resection [ 6 , 7 ] or the scaffold could be used in partial orthotopic transplantation as a way to create a bioartificial liver that ensures metabolic functions while the patient’s own liver regenerates [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, several research groups have been able to fully decellularize simple tissues to whole-livers and demonstrate the ability to repopulate cells into acellular templates for experimental biology research and preclinical applications [137][138][139][140][141][142]. One of the first studies on bioengineering the whole liver using decellularization and recellularization approaches was reported by Uygun et al [142].…”
Section: Liver-derived Acellular Matrix As a Platform For Whole Organ...mentioning
confidence: 99%